LEGAL ANALYSIS OF THE OBLIGATIONS OF ELECTRONIC SYSTEM OPERATORS (PSE) IN PROTECTING THE CONFIDENTIALITY OF ONLINE LOAN BORROWERS' DATA - Rahmad Mirad; Rahmayanti (PT. Radja Intercontinental Publishing, 2026)
Technology-Based Peer-to-Peer Lending Services are a formal form of online lending services initially regulated by POJK No. 10/POJK.05/2022. On the one hand, these online loans make it easier for the public to obtain funds quickly; on the other hand, they also have the potential to harm those involved—for example, the rampant buying and selling of users’ personal data from fintech apps, which recently made headlines on social media. Some sellers of personal data possess thousands to millions of records, including ID cards (KTP), family cards (KK), and even selfies taken with ID cards. Such data breaches should not occur, as personal data within electronic systems is confidential. The research method employed by the author is normative legal research; additionally, this study was conducted using a qualitative approach, focusing on data collection through library research. Electronic System Operators are obligated to maintain confidentiality and security by implementing robust security systems (encryption) to prevent failures in personal data protection. Ultimately, customer data may only be used for the original purpose for which it was collected; Electronic System Operators must not sell or disclose data to third parties for marketing purposes without consent. The misuse of personal data by online lending businesses constitutes an unauthorized act and is explicitly prohibited in the electronic agreement between consumers and the business. Consequently, any actions taken without the consent of both parties constitute a breach of contract and may also be deemed unlawful.